Percepatan Pemenuhan Tenaga Medis dan Tenaga Kesehatan di Puskesmas Untuk Mengoptimalkan Layanan Kesehatan Bagi Masyarakat - Radinal Husein (STIKES Columbia Asia Medan, 2024)
This policy paper examines the problem of still not optimal efforts to fulfill staff at Primary Health Care, which is indicated by the large number of staff vacancies at Primary Health Care, starting from the planning stage to staff placement. Based on the problems above, policy recommendations that can be implemented to accelerate the fulfillment of medical personnel and health workers in Primary Health Care, namely formulating new regulations that regulate the restructuring of the management of medical personnel and health workers as well as regulations that give authority to the Central Government (Menkes) to issue Practice Permits (SIP) so that it can expand the reach of health facilities according to needs The research method used is a descriptive approach from data on the availability of Primary Health Care and the number of health workers from the Ministry of Health, as well as secondary data based on performance report documents and literature studies of other documents from various sources. Accelerating equal distribution of health workers is carried out through cross-sectoral collaboration. Meanwhile, by paying attention to various aspects so that the efforts made can comprehensively encourage the achievement of the desired goals, possible policy options consist of filling health workers in Primary Health Care with the Government Employee with Work Agreement (PPPK) scheme, a policy of redistributing health workers from excess areas to areas that lack certain types of health workers, arranging practice permits, determining incentive indices for health workers, career development for health workers, cross-program and cross-sector collaboration, and fulfilling health facilities in one package with fulfilling health workers. The Ministry of Health and cross-sectoral support in accelerating the fulfillment of medical personnel and health workers in Primary Health Care to formulate new regulations governing the restructuring of the management of medical personnel and health workers as well as regulations that give authority to the Central Government (Menkes) to issue SIPs so that they can expand the reach of health facilities according to needs.